2000
DOI: 10.1093/humrep/15.7.1562
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted semen analysis parameters as predictors for fertility of men from the general population

Abstract: The predictive value of sperm motility parameters obtained by computer-assisted semen analysis (CASA) was evaluated for the fertility of men from general population. In a prospective study with couples stopping use of contraception in order to try to conceive, CASA was performed on semen samples from 358 men. A recently developed CASA system, Copenhagen Rigshospitalet Image house sperm Motility Analysis System (CRISMAS) was used for assessment of motility parameters. This system has an editing function which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
1
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(187 citation statements)
references
References 10 publications
4
177
1
5
Order By: Relevance
“…In our laboratories, we have concentrated on developing a test (Fertell; Bjorndahl et al 2006) based on assessing the concentration of progressively motile sperm, which is one of the most predictive parameters for estimating natural fertility in both sub-fertile (review Tomlinson et al 1999) and normal couples (Larsen et al 2000, Zinaman et al 2000; Fig. 1).…”
Section: Improving and Evaluating The Diagnosis Of Male Fertility Inmentioning
confidence: 99%
“…In our laboratories, we have concentrated on developing a test (Fertell; Bjorndahl et al 2006) based on assessing the concentration of progressively motile sperm, which is one of the most predictive parameters for estimating natural fertility in both sub-fertile (review Tomlinson et al 1999) and normal couples (Larsen et al 2000, Zinaman et al 2000; Fig. 1).…”
Section: Improving and Evaluating The Diagnosis Of Male Fertility Inmentioning
confidence: 99%
“…14,17,18 Sperm motility is well known to be a good predictor of male fertility in vivo and in vitro also and this thing has also been found strongly associated with probability of conception. [19][20][21] Choline acetyl transferase (CAT) is known to facilitate sperm motility and cigarette smoke condensates have CAT inhibitors which lead to reduced sperm motility. 22 Strong relationship has been observed between sperm motility and number of cigarettes smoked per day in a study of Zhang, et al 23 Reduced sperm motility was also found by other researchers in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The four-grade system was underpinned by observations that only sperm with specific motility patterns were able to penetrate the cervical mucus (and therefore enter the female reproductive tract) [20,21]. The advantage of measuring sperm motility in this way has been further supported by the use of computer-assisted sperm analysis (CASA), which has positively correlated the concentration of sperm swimming at > 25 μm per second with the probability of conception [22].…”
Section: Measurement Of Sperm Motilitymentioning
confidence: 99%
“…This view is also shared by delegates attending training courses in the UK organized by the Association of Biomedical Andrologists (http:// www.aba.uk.net), who reported that the assessment of sperm as grade a or b was the most problematic of the practical techniques in semen analysis (personal observation). Perhaps this is unsurprising given that a human observer is being asked to replicate by eye the measurements first made using high-speed cinematographic analysis [20,21] or commercially available CASA systems [22].…”
Section: Measurement Of Sperm Motilitymentioning
confidence: 99%